2023
DOI: 10.1002/mas.21854
|View full text |Cite
|
Sign up to set email alerts
|

Peptides as “better biomarkers”? Value, challenges, and potential solutions to facilitate implementation

Abstract: Peptides carry important functions in normal physiological and pathophysiological processes and can serve as clinically useful biomarkers. Given the ability to diffuse passively across endothelial barriers, endogenous peptides can be examined in several body fluids, including among others urine, blood, and cerebrospinal fluid. This review article provides an update on the recently published literature that reports on investigating native peptides in body fluids using mass spectrometry‐based platforms, specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 141 publications
0
3
0
Order By: Relevance
“…For the definition of urinary peptides significantly associated with trauma, the urinary peptide data of 14 polytraumatized patients and 14 age-and sex-matched healthy controls from the Human Urinary Peptide Database were used (32). This comparison revealed that 281 peptides were significantly affected (p<0.05, Wilcoxon test followed by adjustment for multiple comparisons by Benjamini and Hochberg).…”
Section: Definition Of Urinary Peptides Specific For Polytrauma Patientsmentioning
confidence: 99%
“…For the definition of urinary peptides significantly associated with trauma, the urinary peptide data of 14 polytraumatized patients and 14 age-and sex-matched healthy controls from the Human Urinary Peptide Database were used (32). This comparison revealed that 281 peptides were significantly affected (p<0.05, Wilcoxon test followed by adjustment for multiple comparisons by Benjamini and Hochberg).…”
Section: Definition Of Urinary Peptides Specific For Polytrauma Patientsmentioning
confidence: 99%
“…The peptidome -consisting of thousands of peptides: remnants of protein degradation; specific precursor-derived peptides such as hormones, cytokines, or growth factors; and translation products of small open reading frames (smORFs) [16] responds dynamically to changes in the body, providing a rich source of potential biomarkers. This results in the rapid expansion of peptidomics research observed in recent years [17,18], demonstrating characteristic peptidomic patterns of many diseases, including various types of cancer [19][20][21]. Furthermore, it has been shown that peptidomic analyses can detect statistically significant differences observed in bottom-up proteomics [22].…”
Section: Introductionmentioning
confidence: 98%
“…In that context, naturally occurring peptides might be highly relevant, having the capacity to diffuse passively across endothelial barriers and, as such, sharing important functions in different physiological and pathophysiological processes. 6 Urinary peptides, which are stable as degradation is essentially completed by the time of urination, 6 have been associated with CKD and heart disease, including coronary artery disease (CAD) and HF, and provide prognostic information. 6,7 In CKD, for example, in a multicenter, prospective, observational study with embedded randomized controlled trial (Proteomic Prediction and Renin Angiotensin Aldosterone System Inhibition Prevention Of Early Diabetic nephropathy In Type 2 Diabetic Patients With Normoalbuminuria [PRORITY] trial), urinary peptides were used to identify high-risk patients who may benefit from early interventions.…”
mentioning
confidence: 99%
“…6,7 In CKD, for example, in a multicenter, prospective, observational study with embedded randomized controlled trial (Proteomic Prediction and Renin Angiotensin Aldosterone System Inhibition Prevention Of Early Diabetic nephropathy In Type 2 Diabetic Patients With Normoalbuminuria [PRORITY] trial), urinary peptides were used to identify high-risk patients who may benefit from early interventions. 6…”
mentioning
confidence: 99%
See 1 more Smart Citation